College-Readiness and Academic Preparedness: The Same Concepts? - Wally Barnes; John R Slate; Ana Rojas-LeBouef (Arizona State University, 2010)
The purpose of this literature review is to examine the issue of college-readiness as it relates to the concept of academic-preparedness. With President Obamaâs emphasis on changing the No Child Left Behind Act to a focus on college- and career-readiness, an examination of college-readiness is merited. Within the last several decades, academically rigorous curriculum and stringent accountability measures have been mandated by state and federal legislation in hopes of increasing the likelihood of students graduating from high school college-ready. A question that remains unanswered is the extent to which high school graduates are more academically prepared based on core curriculum and a one-size-fits-all standardized testing regime rather than being college-ready. The politics of education, including national reports and legislative acts, was examined and discussed to shed light on the issue of college-readiness. In a review of the plethora of college-readiness literature, college-readiness should, in all likelihood, be defined as academic preparedness.